Laxness’s wives tell their stories - Bragason, Úlfar (Folia Scandinavica Posnaniensia, 2007)
No twentieth-century Icelandic author has enjoyed success and popularity to rival that of Halldor Laxness. At the end of his writing career, Laxness wrote four books which he called “novels in essay form” or essais-romans, but which are generally considered to be memoirs, written with artistic licence. These books are: 7 tuninu heima (In the Field at Home) (1975), tJngur eg var (Young was I) (1976), Sjomeistarasagan (The Story of Seven Masters) (1978), and Grikklandsarid (The Year of Greece) (1980). They cover only a fraction of the author’s life, up to the age of twenty. Readers have learned of his subsequent experiences mostly through countless articles and interviews in the press, on radio and television. Laxness has, at least since winning the Nobel Prize for Literature in 1955, been a public personality, although he has been reticent about his private life.